PEMBERDAYAAN EKONOMI BAGI LEMBAGA MISI LOKAL MELALUI USAHA JASA LAUNDRY - Tameon, S.M.; Ully, I.S.; Wila, A.; Suni, H.; Natonis, I. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i04.p12, 2023)
This Community Service aims to develop the 'missionpreuner' concept to motivate partners to be economically empowered to support the missionary programs and family economy well-being by doing the laundry service business. The method used in this study is the science and technology diffusion with a participatory approach implemented through lectures, discussions, question and answer, practice, and mentoring. The activity began with sharing the missionary program from the Soe Local EE Team and the socialization on the 'missionpreuner' concept. Then the community service team introduced and conducted demos on the use of equipment for the laundry business, such as using washing machines, drying, ironing (steam or electricity), digital scaling, tagging devices or clothing markers, folding techniques and clothes packaging. The results show that the partners are enthusiastic about learning about the laundry service because it will help them financially in carrying out missionary works in the region. The evaluation proved the laundry service business results were very satisfying. Keywords: Empowerment, Mission preuner, Laundry